Microparticle‐Based Soft Electronic Devices: Toward One‐Particle/One‐Pixel. (1st May 2019) - Hwang, Hyejin; Jeong, Unyong
Abstract: While microparticle (MP) assemblies have long attracted academic interest, few practical applications of assembled MPs have been achieved because of technological difficulties related to MP synthesis, MP position registration, and the absence of device concepts. The precise positioning of functional MPs in a proper stencil can produce flexible/stretchable electronic devices, even when the MPs themselves are rigid. In recent years, remarkable progress has been made in the programmable position registration of MPs, production of functional MPs, and concepts for MP‐based, pixel‐type electronic devices. This progress report reviews the recent technological advances in MP assembly and discusses the technological challenges preventing the realization of the one‐particle/one‐pixel concept. Abstract : Recent advances in accurate position registration of microparticles (MPs), production of functional MPs, and MP‐based pixelated electronic devices are presented. The technological challenges to implement the concept of "one‐particle/one‐pixel" are also discussed.